Cell‐Free DNA Blood Collection Tubes Are Appropriate for Clinical Proteomics: A Demonstration in Colorectal Cancer. Issue 3 (30th March 2018) - Almazi, Juhura G.; Pockney, Peter; Gedye, Craig; Smith, Nathan D.; Hondermarck, Hubert; Verrills, Nicole M.; Dun, Matthew D.
Abstract : Background: Optimized blood collection tubes (BCT) have been developed to expand the utility of plasma cell‐free DNA (cfDNA) and are in clinical use. The appropriateness of plasma collected and stored in these tubes for proteomic analysis is unknown. Methods: Paired blood samples were collected in BCT and traditional K3EDTA (EDTA) tubes from healthy controls and from colorectal cancer (CRC) patients before and after surgery, and stored for between 45 min and 48 h at room temperature. Plasma proteins were analyzed following high‐abundant plasma protein depletion in quantitative discovery and targeted proteomics by liquid chromatography tandem‐mass spectrometry (LC‐MS/MS). Results: BCT reduced cellular protein contamination in healthy controls over time, and increased the number of high confident low‐abundant protein identifications in CRC blood samples compared to matched samples collected in EDTA tubes. The known CRC plasma protein biomarker, carcinoembryonic antigen (CEA), showed elevated levels across patients pre‐operatively when collected and stored in BCT compared to EDTA tubes. Emerging CRC biomarkers, Dickkopf‐3 (DKK3) and Gelsolin (GSN), showed elevated levels pre‐operatively when collected in BCT. Conclusions: Optimized BCT are appropriate for low‐abundant plasma protein analysis and can be used with confidence for clinical proteomics.